King of the wind - Henry, Marguerite, 1902-1997 (Simon & Schuster Books for Young Readers, 2001)
Sham and the stable boy Agba travel from Morocco to France to England where, at last, Sham's majesty is recognized and he becomes the "Godolphin Arabian," ancestor of the most superior Thoroughbred horses.